What is The Effect of Early Surgical Stabilization of Rib Fractures Compared to Conservative Management on Pain Control and Pulmonary Function in ICU Patients? : A Systematic Review - Landong Sijabat; Raka Jati Prasetya; Mutia Juliana (The International Journal of Medical Science and Health Research, 2026)
Introduction: Rib fractures, especially flail chest and multiple displaced fractures, cause severe pain and respiratory dysfunction, often requiring ICU admission. The optimal management—early surgical stabilization (SSRF) versus conservative treatment—remains debated. Methods: This systematic review synthesized 80 studies (RCTs, etc) comparing early SSRF (≤72 hours) to conservative management in adult ICU patients with rib fractures. Outcomes focused on pain control, pulmonary function, and clinical endpoints. Results: Early SSRF significantly reduced pain scores at 2 weeks (NPS 2.9 vs. 4.5, p<0.01) [1] and lowered opioid requirements (155 vs. 246 morphine milliequivalents, p<0.001) [3]. Pulmonary benefits included shorter mechanical ventilation (mean difference -4.52 days) [4], reduced pneumonia (RR 0.57) [11], and fewer tracheostomies (OR 0.25) [4]. ICU stay decreased by ~4 days [8], and mortality improved (OR 0.3) [8]. Early intervention (≤72h) was superior to delayed surgery [21,25]. Benefits were most pronounced in flail chest, elderly, and mechanically ventilated patients [13,14,43]. Discussion: SSRF provides rapid pain relief, improves respiratory mechanics, and reduces complications, but outcomes depend on timing, patient selection, and injury pattern. Heterogeneity exists, with non-flail fractures showing less consistent benefit [19]. Conclusion: Early SSRF (within 72 hours) significantly improves pain, pulmonary function, and survival in high-risk ICU patients with severe rib fractures. Delayed surgery loses advantage. Future RCTs should standardize timing and subgroups.